After i do ebook A novel. - Reid, Taylor Jenkins (2014)
From the New York Times bestselling author of The Seven Husbands of Evelyn Hugo "A seductive twist on the timeless tale of a couple trying to rediscover love in a marriage brought low by the challenges of domestic togetherness...touching, perceptive, and achingly honest." —Beatriz Williams, New York Times bestselling author When Lauren and Ryan's marriage reaches the breaking point, they come up with an unconventional plan. They decide to take a year off in the hopes of finding a way to fall in love again. One year apart, and only one rule: they cannot contact each other. Aside from that, anything goes. Lauren embarks on a journey of self-discovery, quickly finding that her friends and family have their own ideas about the meaning of marriage. These influences, as well as her own healing process and the challenges of living apart from Ryan, begin to change Lauren's ideas about monogamy and marriage. She starts to question: When you can have romance without loyalty and commitment without marriage, when love and lust are no longer tied together, what do you value? What are you willing to fight for? This is a love story about what happens when the love fades. It's about staying in love, seizing love, forsaking love, and committing to love with everything you've got. And above all, After I Do is the story of a couple caught up in an old game—and searching for a new road to happily ever after.